PRACTICAL ASPECTS OF THE ARTIFICIAL URINARY SPHINCTER IN MEN (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The artificial urinary sphincter (AUS) remains the gold standard in moderate to severe urinary incontinence after prostatic surgery. Starting from the significant personal experience of the authors in the field, we aim to review the current indications, limits and challenges associated with the implantation of an AUS. We present different surgical approaches and pre- and postoperative considerations.
Keywords: Artificial urinary sphincter; Intrinsic sphincteric deficiency; Urinary incontinence; Post prostatectomy incontinence